Scaling Up Blended Financing of Water and Sanitation Investments in Kenya - Advani, Rajesh (World Bank, Washington, DC, 2016)
This note looks at a series of interventions undertaken by the Government of Kenya, with support from the World Bank and other development partners, to improve access to commercial finance in the water and sanitation sector. It describes recent sector reforms and innovative financing initiatives and draws lessons from interventions supporting utility and community water service providers in accessing finance for infrastructure investment.